Operative Thoracic Surgery. - Kaiser, Larry R. (London : CRC Press, 2017)
Over a decade after the last edition, Operative Thoracic Surgery, Sixth Edition has been thoroughly revised and updated by a team of prestigious international contributors. Particular emphasis is given to new and emerging techniques, particularly minimally invasive procedures, ensuring that the book remains an essential resource for surgeons in training, residents and fellows in thoracic and esophageal surgery, and fully qualified practitioners needing a definitive reference. Additional text describes the principles and justification of choosing each procedure, pre-operative assessment and preparation, post-operative care and outcomes.
OCLC-licensed vendor bibliographic record.
Keywords: Chest -- Surgery